Isolation of the Individual Substance Liquiritin from the Plant Glycyrrhiza Glabra L (The Peerian Journal, 2023)
The individual substance liquiritin was isolated from the root of the plant Glycyrrhiza glabra L. The extraction was carried out in a water bath equipped with a reflux condenser for 2 hours at a temperature of 40-50 oC. To extract the residue of lipophilic substances and chlorophyll, the aqueous extract was treated with chloroform in a ratio of 1:4. The purified aqueous extract was fractionated with ethyl acetate, the fractions were separated on a separating funnel. All of the above fractions were concentrated on a rotary evaporator to a residue of 1/10. Ethyl acetate fractions were precipitated with hexane in ratios from 1 : 1 to 1 : 5.